2018
DOI: 10.1186/s13104-018-3923-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality, sexually transmitted infections and contraception among health sciences students in university of Lomé, Togo

Abstract: ObjectivesEvaluate the practice of sexuality, contraception and the risk of sexually transmitted infections among students in the Faculty of Health Sciences, University of Lomé, Togo.ResultsThree hundred and sixteen (316) students were interviewed, with a response rate of 43.3%. The average age of students completing the form was 21.4 ± 2.7 years and their sex ratio was 2.2. Of this number of students who completed the form, 51.8% have already had sex. The mean age of first intercourse was 17.9 ± 3.2 years; 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The study participants' sociodemographic characterization regarding sex, age, and relationship status was similar to that found in other studies (Heredia et al, 2017;Spindola et al, 2020;Darré et al, 2018). The use of alcohol as a determinant of risky for Revista de Enfermagem Referência 2022, Série V, nº9: e21043 DOI: 10.12707/RV21043…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The study participants' sociodemographic characterization regarding sex, age, and relationship status was similar to that found in other studies (Heredia et al, 2017;Spindola et al, 2020;Darré et al, 2018). The use of alcohol as a determinant of risky for Revista de Enfermagem Referência 2022, Série V, nº9: e21043 DOI: 10.12707/RV21043…”
Section: Discussionsupporting
confidence: 81%
“…Considering the consistency of condom use among young people, an international study conducted with 316 university students over 18 years old in West Africa revealed that 51.8% of the participants had already started their sexual life, with their sexual debut occurring at a mean age of 17.9 (SD = 3.2 years), 48.5% had more than one sexual partner, with 15.9% of these having had at least five sexual partners, and 67.5% reported using at least one contraceptive method during sexual intercourse (Darré et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations